Lake metabolic processes and their effects on the carbonate weathering CO2 sink: Insights from diel variations in the hydrochemistry of a typical karst lake in SW China. (15th August 2022) - He, Haibo; Wang, Yuyouting; Liu, Zaihua; Bao, Qian; Wei, Yu; Chen, Chongying; Sun, Hailong
Highlights: Diel lake hydrochemical variations and the coupled carbon cycling were observed. These processes were controlled mainly by lake metabolic processes. High DIC in a karst lake may support high primary production. The carbon sink by the coupled carbonate weathering reached 650–704 t C km −2 yr −1 . A karst aquatic system can maintain net autotrophy. Abstract: The precipitation of carbonate minerals does not invariably result in CO2 emission to the atmosphere, because dissolved inorganic carbon (DIC) can be partially utilized by terrestrial aquatic phototrophs, thus generating an autochthonous organic carbon (AOC) sink. However, little is known about the potential effects of this mechanism on carbon cycles in DIC-rich lakes, mainly due to the lack of detailed documentation of the related processes, which limits our ability to accurately evaluate and predict the magnitude of this carbon sink. We conducted field observations in Fuxian Lake, a large and representative karst lake in the Yunnan-Guizhou Plateau, SW China. Continuous diel monitoring was conducted to quantitatively assess the coupled relationship between lake metabolism and DIC cycling and its influence on the carbonate weathering-related CO2 sink. We found that the diel physicochemical variations and isotopic characteristics were mainly controlled by the metabolism of aquatic phototrophs, evidenced by a significant relationship between net ecosystem production and diel DIC cycling, and demonstrating the significance of DIC fertilization in supporting high primary production in karst lakes. The data showed that a reduction in photosynthesis occurred in the afternoon of almost every day, which can be explained by the lower CO2 /O2 ratio that increased the potential for the photorespiration of aquatic plants, thus reducing photosynthesis. We found that a net autotrophic ecosystem prevailed in Fuxian Lake, suggesting that the lake functions more as a sink than a source of atmospheric CO2 . Considering carbonate weathering, the estimated AOC sink amounted to 650–704 t C km −2 yr −1, demonstrating both the potentially significant role of metabolism in lacustrine carbon cycling and the potential of the combination of photosynthesis and carbonate weathering for carbon sequestration. Our findings may help to quantitatively estimate the future impact of lake metabolism on carbon cycling, with implications for formulating management policies needed to regulate the magnitude of this carbon sink. Graphical abstract: Image, graphical abstract